A oficina do diabo e a casa do senhor: os embates identitários dentro dos presídios - Vinicius Assis Couto (2011)
The possibility of a prisoner to survive in a prison is through the successful transition into the formal rules of the institution associated with the rules made by the prisoners themselves. The latter, established and reaffirmed for decades, are so legitimized, and enforced by inmates who makes it possible to ascertain the existance of a singular intramural society. Able to create its own mechanism of punishment, as well as its hierarchy and rules of conduct, the intramural society, generally does not allow its participants to break their rules. However, in recent decades has emerged within this society, a specific group of prisoners with moral values and ethical conduct discrepant of the ones dominants in this Intramural society: protestants. The emergency, interaction and integration of this new group in the hierarchical structure of intramural society make up the issue of this dissertation. Using observation and interviews with prisoners and prison officials, this dissertation shows that sometimes the group of evangelical prisioners breaks with their own doctrines in order to maintain its acceptance in the intramural society